Sustainable leadership skills needs of brick/block-laying and concreting (BBC) students for self-reliance in government technical colleges of Kano State - Ya’u, Isyaku; Angulu , Haruna; Hamza , Samaila; Chedi, J. Mustapha (Kashere Journal of Education, 2023)
This study determined the sustainable leadership skills need of brick/block laying and concreting students for self-reliance in technical colleges of Kano State, Nigeria. Two research objectives, two research questions and one null hypothesis guided the study. Descriptive survey research design was adopted for the study. The study had a total population of 1,344 respondents with a sampled size of 302 respondents using stratified random sampling technique. The instrument used for gathering data for the study was a structured questionnaire. The instrument was validated by three experts. Cronbach Alpha statistical tool was used to determine the reliability coefficient of 0.88. A total of 302 copies of the instrument were administered to the respondents, however, 296 copies were returned filled. This brings the percentage return rate to 98%. Mean and standard deviation statistical tools were employed to analyze the research questions. While t-test statistical tool was used to test the null hypothesis at 0.05 level of significance. The findings of the study revealed that Brick/Block Laying and Concreting (BBC) Trade students of the study area need sustainable leadership skills that will enable them to coordinate, supervise, budget, maintain good financial records, work together as team and implement policies in their prospective place of work, to enable them fit into the world of work effectively. It was therefore recommended that government should ensure that appropriate policies that will facilitate the training need of BBC students in the area of sustainable leadership skills that will enable them fit into the construction industry should be duly emphasized in the curriculum of Brick/Block Laying and Concreting Trade.